Transformations in Cuban Agriculture After 1959 - José Alvarez (EDIS)
The Cuban government that took power on January 1, 1959, was going to drastically change rural Cuba. This fact sheet describes the most important agricultural policies during the 1959-1989 period, although in some instances it is necessary to mention events and policies before and after that period. A careful examination of the multitude of policies and agricultural organizations implemented during those 30 years provides an understanding of the confusion arising from the fact that Karl Marx did not leave an implementation blueprint to his followers. This is EDIS document FE481, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published July 2004.